Hematoma Block Verses General Anesthesia For Close Reduction And Percutaneous Pinning Of Distal Radius Fractures In Elderly Patients - Muhammad Zahid Siddiq; Tooba Tahir; Waqas Ali; Rahman Rasool Akhtar; Mohammad Saleem; Nisar Ahmad (Journal of Rawalpindi Medical College)
Objective: The objective of our study is to compare two techniques used for analgesia, hematoma block and general anaesthesia, in patients presented with a fracture of the distal radius in the trauma centre of Aziz Bhatti Shaheed Hospital Gujrat.